2020
DOI: 10.1186/s13287-020-01809-1
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic therapy with human amniotic fluid stem cells improved survival in a rat model of lipopolysaccharide-induced neonatal sepsis through immunomodulation via aggregates with peritoneal macrophages

Abstract: Background Despite recent advances in neonatal care, sepsis remains a leading cause of mortality in neonates. Mesenchymal stem cells derived from various tissues, such as bone marrow, umbilical cord, and adipose tissue, have beneficial effects on adult sepsis. Although human amniotic fluid stem cells (hAFSCs) have mesenchymal stem cell properties, the efficacy of hAFSCs on neonatal sepsis is yet to be elucidated. This study aimed to investigate the therapeutic potential of hAFSCs on neonatal sepsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 19 publications
(26 citation statements)
references
References 50 publications
4
22
0
Order By: Relevance
“…Although concerns have been raised that improved survival of infants treated with hAFSCs might be accompanied by an increase in disabling morbidity in neonatal sepsis survivors, in this study, we found that prophylactic therapy with hAFSCs improved cognitive impairment in neonatal sepsis survivors at adolescence in rats. Together with our findings in a previous study [ 14 ], herein, we prove that hAFSC treatment improves mortality and morbidity in neonatal sepsis. The treatment suppresses acute reactive gliosis, such as astrocyte and microglial activation, and subsequently reduces astrogliosis in the hippocampal region for a long time, and could result in a favorable long-term neurological outcome.…”
Section: Discussionsupporting
confidence: 90%
See 4 more Smart Citations
“…Although concerns have been raised that improved survival of infants treated with hAFSCs might be accompanied by an increase in disabling morbidity in neonatal sepsis survivors, in this study, we found that prophylactic therapy with hAFSCs improved cognitive impairment in neonatal sepsis survivors at adolescence in rats. Together with our findings in a previous study [ 14 ], herein, we prove that hAFSC treatment improves mortality and morbidity in neonatal sepsis. The treatment suppresses acute reactive gliosis, such as astrocyte and microglial activation, and subsequently reduces astrogliosis in the hippocampal region for a long time, and could result in a favorable long-term neurological outcome.…”
Section: Discussionsupporting
confidence: 90%
“…LPS administration induced neuroinflammation in the rat brain, as indicated by GFAP-and ionized calcium-binding adapter molecule 1 (Iba-1)-positive cells. As reported previously [14], LPS injection elicited neuroinflammation 48 h after LPS exposure, whereas the inflammatory changes were significantly attenuated by hAFSC treatment. Although we previously reported a reduction in neuroinflammation in the entire hippocampus after hAFSC treatment, in this study, we analyzed neuroinflammation in three hippocampal regions, viz., CA1, CA3, and dentate gyrus (DG).…”
Section: Hafsc Administration Reduced the Glial Fibrillary Acidic Prosupporting
confidence: 85%
See 3 more Smart Citations